1995
DOI: 10.2527/1995.73113476x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of barley variety and dietary barley content on digestive function in beef steers fed grass hay-based diets

Abstract: Five ruminally and duodenally cannulated steers were used in a 5 x 5 Latin square design with a 2 x 2 + 1 arrangement of treatments to study the effects of barley variety and dietary barley content on digestive function in steers fed grass hay-based diets. Barley varities evaluated were Russell and Steptoe, which had bulk densities of 67.7 and 64.5 kg/hL, respectively. Supplemental treatments were as follows: corn, low Russell (Ru-lo), low Steptoe (St-lo), high Russell (Ru-hi), and high Steptoe (St-hi). Corn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
6
14
2
Order By: Relevance
“…Increasing the level of barley in the diet resulted in a linear increase (P < 0.05) in total VFA levels at 1000 and 1400 h (Table 3). Our results are consistent with other studies which showed reduced ruminal pH and increased total VFA levels as the amount of rapidly fermented carbohydrate from barley grain in the diet increased (McAllister et al 1990;Feng et al 1995;Hatfield et al 1997).…”
Section: Metabolism Trialsupporting
confidence: 93%
“…Increasing the level of barley in the diet resulted in a linear increase (P < 0.05) in total VFA levels at 1000 and 1400 h (Table 3). Our results are consistent with other studies which showed reduced ruminal pH and increased total VFA levels as the amount of rapidly fermented carbohydrate from barley grain in the diet increased (McAllister et al 1990;Feng et al 1995;Hatfield et al 1997).…”
Section: Metabolism Trialsupporting
confidence: 93%
“…The duodenal flow measurements, however, did not support this hypothesis, as ruminal OM and NDF digestibilities were not statistically different between the two diets. The observed higher ruminal ammonia concentration in the heifers fed the barley diet was a result of increased N intake with this diet and greater ruminal degradability of soybean meal compared to corn gluten meal (Reynal and Broiderick 2003) and of barley grain vs. corn grain CP (Reynolds et al 1993;Feng et al 1995). The increased concentrations of total VFA and acetate with the barley diet indicate a more intensive microbial fermentation compared with the corn-based diet, and agrees with existing literature (Martin-Orue et al 2000b;Khorasani et al 2001;Hristov et al 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Composition of the diets may have also influenced MN flow. Compared to corn, barley increased MCP production in some studies (Feng et al 1995), but not in others (Casper et al 1999). Excretion of allantoin and uric acid in the urine did not indicate a significant effect of grain type on MCP measured using the urinary PD method.…”
Section: Discussionmentioning
confidence: 92%
“…One hundred grams of grass hay chopped to 19 mm and labeled with Yb were mixed with digesta contents and put back into the rumen via the cannula. The hay was labeled with Yb by soaking it in 100 mL of a solution containing 3.89 g of Yb(NO 3 ) 3 .5H 2 O and allowing the hay to dry overnight at room temperature (Feng et al 1998).…”
Section: Passage Ratesmentioning
confidence: 99%